2016
DOI: 10.4028/www.scientific.net/amm.848.35
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Welding Repair Parameters of Tube 35Cr-45Ni-Nb Alloy of the Ethylene Heating Furnace

Abstract: The aim of this research is to study the effects of welding repair parameters on weld joint of tube 35Cr-45Ni-Nb alloy by using the Gas Tungsten Arc Welding (GTAW) process of two different base metals. One was a new tube material and other was a used tube treated with carburized condition. The 35Cr-45Ni filler metal was sellected for welding repair experiments. The SEM-EDS analysis was used to observe a segregation of atom in the used tube specimen. The non-destructive examination (NDE) tests were done to chec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…As the weldability of the ethylene pyrolysis furnace tubes is deteriorated due to microstructure deterioration [18,19], carburisation and oxidation [20] in the service process, many researchers have studied welding repair parameters of ethylene cracking furnace tubes after a long-term service [21][22][23]. As the weak part of the ethylene pyrolysis furnace tube, the microstructure and mechanical properties of the Cr35Ni45Nb alloy weld joint after service are rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…As the weldability of the ethylene pyrolysis furnace tubes is deteriorated due to microstructure deterioration [18,19], carburisation and oxidation [20] in the service process, many researchers have studied welding repair parameters of ethylene cracking furnace tubes after a long-term service [21][22][23]. As the weak part of the ethylene pyrolysis furnace tube, the microstructure and mechanical properties of the Cr35Ni45Nb alloy weld joint after service are rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Saavedra et al [2] suggested that there are several factors causing the coke formation such as operating loads, temperature, time, heat flow and the partial pressure of the hydrocarbon. In our previous work [3], the 35Cr-45Ni-Nb tube can be magnetized by the carburization process. The microstructure in the carburized tube shows a large amount of areas with fractions of precipitated complex carbides of (Cr,Mn) 23 C 6 and SiC.…”
Section: Introductionmentioning
confidence: 99%